2004
DOI: 10.1002/adfm.200305139
|View full text |Cite
|
Sign up to set email alerts
|

Poled Sol–Gel Materials With Heterocycle Push–Pull Chromophores that Confer Enhanced Second‐Order Optical Nonlinearity

Abstract: Hybrid organic-inorganic materials doped with zwitterionic push-pull chromophores with high hyperpolarizability have been synthesized by a sol-gel procedure. A large chromophore concentration was reached by using N-(hydroxyethyl)carbazole as a physical spacer (preventing the dye aggregation). Spain-coated doped films were electrically poled and second harmonic generation measurements performed in situ. During the thermally assisted polling under a N-2 atmosphere,only the carbazole molecules degraded. Second-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…This facilitates the orientation of the molecules inside the dried matrix, not yet completely reticulated, allowing their fast alignment. The temporal stability of chromophores orientation is under investigation, but from previous results on similar sol -gel systems seems to be quite good [11]. This result is due to the progress of network reticulation during poling process: FT-IR spectra (not showed) prove a decrease of the OH band and the disappear of the epoxide signal due to the reaction of the amine group with the epoxy ring, favored by the thermal treatment of the matrix, during the poling process.…”
Section: Doped Films Preparation and Polingmentioning
confidence: 79%
See 1 more Smart Citation
“…This facilitates the orientation of the molecules inside the dried matrix, not yet completely reticulated, allowing their fast alignment. The temporal stability of chromophores orientation is under investigation, but from previous results on similar sol -gel systems seems to be quite good [11]. This result is due to the progress of network reticulation during poling process: FT-IR spectra (not showed) prove a decrease of the OH band and the disappear of the epoxide signal due to the reaction of the amine group with the epoxy ring, favored by the thermal treatment of the matrix, during the poling process.…”
Section: Doped Films Preparation and Polingmentioning
confidence: 79%
“…SHG measure is performed in situ, during polarization of the doped films, and previous measures has demonstrated that value of d 33 up to 70 pm/V can be obtained [11]. By using GDMMS precursor to prepare hybrid the matrix, after 20 min the SHG signal reaches the maximum value, while the poling of the chromophores in the solid sol -gel hybrid materials is obtained in a times of a few hours if GPTMS is used.…”
Section: Doped Films Preparation and Polingmentioning
confidence: 99%
“…To overcome such limitation, the hybrid matrix was co-doped with an N-(Hydroxyethyl)-carbazole (CbOH) acting as a physical spacer to decrease the aggregation of the chromophores at large loading levels (20%) [28]. After corona poling (standard condition for 4 hours of at 140 • C) a value of the NLO coefficient d 33 of 70 pm/V was measured.…”
Section: Tablementioning
confidence: 99%
“…In this article, we want to enlarge the varieties of materials that can be used in this type of technique. We investigated if this technique was applicable to aromatic diazo groups linked silicon sol (ADS), as inorganic materials are usually more stable than organic polymers [53][54][55][56], its applications would be extended widely. We selected ADS as polycation, and LMWC molecule of 2-({4-[4-(2-carboxy-2-cyano-vinyl)-phenylazo]-phenyl}-methyl-amino)-ethyl acid (DRCB) as anion to fabricate multilayer films under electric field, and followed by photochemical reaction to achieve cross-linked structure.…”
Section: Introductionmentioning
confidence: 99%